'Parallel Emergencies' in Italy and Australia: Marginalised and Racialised Romani and Aboriginal 'Camp Dwellers'. (3rd September 2017) - Armillei, Riccardo; Lobo, Michele
ABSTRACT: This paper focuses on Romani and Aboriginal peoples who live at the margins of Italian and Australian societies, often in city 'camps' that show signs of institutional abandonment, neglect and extreme decay. To address this socio-economic disadvantage and improve the quality of life, the governments of these two countries have implemented what we have defined 'parallel emergencies', extraordinary policy measures of intervention, surveillance and control. This paper argues that these policies that aim to improve the everyday lives of Romani and Aboriginal peoples, however, often re-produce a 'tradition' of institutionalised racism that can be traced back to the post-Unification period in Italy and the Federation period in Australia. By drawing on the work of Giorgio Agamben, we highlight the approach adopted by Italian and Australian institutions in terms of 'inclusive exclusion'. On the one hand, the government makes significant investment in schooling and employment projects; on the other, it keeps promoting the use of emergency measures, which leaves slender scope for Romani and Aboriginal voices.